(untitled) (Research, Society and Development, 2020)
This article arises from a bibliographic research, carried out with the objective of presenting the way the fields of knowledge of human physiology and exercise physiology were inserted in the basic education curriculum, mainly in the disciplines of Science and Physical Education in Elementary School . For this purpose, books, magazines, and articles in the areas of Natural Sciences, Medicine and Physical Education were used as sources, as well as documents from archives and institutions, available at SciELO and Google Scholar. In this process, remarkable historical facts about the construction of the concepts of physiologies are recovered. The results point to a long process that spans centuries, exposing different historical lines, conceptions about the human body and its development. Finally, from a content analysis, we found that the process of inserting physiologies in basic education begins with laboratory experiments that instigate studies at universities, so that later on, this knowledge of the laboratories could be transformed into fields of study. knowledge in universities and thus gradually inserted into basic education.